A Study of Teak Wood Quality from Community Forests in Gunungkidul. V.Wood Chemical Properties - Ganis Lukmandaru; Arsyi Rahman Mohammad; Pito Wargono; Vendy Eko Prasetyo (Jurnal Ilmu Kehutanan)
This study aimed to explore the chemical properties of teak wood grown in community forests from Gunungkidul Regency. Trees (dbh 28-37 cm) were selected from three different sites i.e. Nglipar, Panggang, and Playen. Three trees were cut from each site and disks were taken from the base of the trees. The disk in radial cross section was divided into 3 parts: sapwood, outer heartwood, and inner heartwood. Chemical properties tested were holocellulose, á-cellulose, hemicellulose, lignin, ethanol-toluene extractives, hot-water soluble extractives, solubility in NaOH 1%, and ash contents. Mature teakwoods from Randublatung (Perhutani plantation) were used for comparison purpose.The values range of chemical composition in the cell wall components of the Gunungkidul teak wood were holocellulose content 75.76-79.74%, , á-cellulose content 46.72-50.90%, hemicellulose content 27.41-30.14%, lignin content 29.22-32.80%, and solubility in NaOH 1% 16.43-17.35%. Further, the ethanol-toluene extractive, hot-water soluble, and ash content values ranged from 5.04 to 10.77%, 2.74-7.85%, and 0.60-1.66%, consecutively. Interaction between two factors affects significantly to holocellulose, á-cellulose, hemicellulose, and ethanol-toluene extractive contents. The growth-site significantly influence on the ash contents as radial factor has significantly affect on the levels of hot water soluble extractives and ash content. The amounts of ethanol-toluene extractive and ash contents of Gunungkidul teak wood showed the lower values than those of teak from Randublatung. The values of other parameters were remain in the range of value of teak from Randublatung.